Tutorial : distributed system design - 366434 Mariani, Michael P.; Palmer, David F.; Initially presented at the First International Conference on Distributed Computing Systems October 1-4, 1979; Huntsville, Alabama (New York : Institute of Electrical and Electronics Engineers, 1979)
57